Optimization of the Polymerase Chain Reaction for Detecting Sheep Pox Virus in Alzawiyah City, Libya - Salem Khalifa; Almabrouk Fares; Imad Buishi; Khadega Alazoumi; Tarek Abukreba; Abdulati Salem; Inas Alhudiri; Mahmud Abushhewa (AlQalam Journal of Medical and Applied Sciences, 2025)
Accurate and rapid diagnosis of SPV is essential to control the rapid spread of disease in Libya. This study was designed to optimize and develop a PCR assay for sheep pox virus identification in sheep farms in Alzawiyah City, Libya. A total of 120 oral swab samples were collected as follows: clinically suspected sheep pox (n=67), clinically suspected Contagious Ecthyma (n=18), and healthy sheep (n=35). The collected samples were subjected to DNA extraction followed by a polymerase chain reaction targeting the P32 gene with specific primers. All 67 clinically suspected sheep pox samples were found positive for SPV and yielded expected amplicon sizes of 390 bp. All the clinically suspected Contagious Ecthyma (CE) samples and healthy samples were negative. The result of the current P32 gene-based PCR assay demonstrated good sensitivity and specificity and could be used for molecular diagnosis of sheep pox disease. التشخيص الدقيق والسريع لفيروس الجدري البقري ضروري للسيطرة على الانتشار السريع للمرض في ليبيا. صُممت هذه الدراسة لتحسين وتطوير اختبار تفاعل البوليميراز المتسلسل لتحديد فيروس الجدري البقري في مزارع الأغنام في مدينة الزاوية، ليبيا. تم جمع ما مجموعه 120 عينة مسحة فموية على النحو التالي: جدري الأغنام المشتبه به سريريًا (ن = 67)، والإكثيما المعدية المشتبه بها سريريًا (ن = 18)، والأغنام السليمة (ن = 35). خضعت العينات المجمعة لاستخراج الحمض النووي متبوعًا بتفاعل البوليميراز المتسلسل الذي يستهدف جين P32 باستخدام بادئات محددة. تم العثور على جميع عينات جدري الأغنام المشتبه بها سريريًا والبالغ عددها 67 إيجابية لفيروس الجدري البقري وأسفرت عن أحجام أمبليكون متوقعة تبلغ 390 زوجًا قاعديًا. كانت جميع عينات الإكثيما المعدية المشتبه بها سريريًا والعينات السليمة سلبية. أظهرت نتيجة اختبار تفاعل البوليميراز المتسلسل الحالي القائم على جين P32 حساسية وخصوصية جيدتين ويمكن استخدامها للتشخيص الجزيئي لمرض الجدري البقري